The occurrence of sexual Chara canescens (Charales, Charophyceae) in Sardinia (Italy). Issue 1 (2nd January 2019) - Nowak, Petra; van de Weyer, Klaus; Becker, Ralf
ABSTRACT: Chara canescens Loisel. is the only haplostichous charophyte species in Europe. Populations with parthenogenetically reproducing females have been described from several European locations. In contrast, populations with female and male individuals are known only from a few European sites. Male individuals of C. canescens were recently found in Sardinia (Italy) and studied by analysis of rbc L and matK gene sequences. Phylogenetic analysis demonstrated that all European samples of C. canescens formed a robust monophyletic group, in which the bisexual samples can be differentiated from parthenogenetic populations by rbc L and matK gene sequences. It was shown that the bisexual C. canescens, originated from Sardinia and Neusiedler See-Seewinkel (Austria), can be distinguished based on rbc L gene sequence data. Further vegetation surveys and a larger sample size will be needed to determine the degree of genetic diversity within and between the reproductive modes of C. canescens .